(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article presents an analytical review of the systems of external independent evaluation of preschool education quality in the United States and Singapore. Special attention is given to the specifics of the National Association for the Education of Young Children (NAEYC) as well as programs like STARS (Pennsylvania, USA) and SPARK (Singapore). The key characteristics of external quality assessment in these countries include voluntary participation, the presence of a PR component (so that parents understand how to navigate in a variety of kindergartens), support of leadership qualities and training managers within organizations, the use of standardized rating scales (eg, ECERS-R), which have been recognized by the international community and focus more on evaluating environmental performance rather than children’s results. So the review of the foreign practices of organizing pre-school education quality assessment helps us to better understand how to form our national system of independent expert examination of pre-school education in the most productive way